Number of progeny number and accuracy of breeding value in productive traits of alpacas. A simulation study - Mamani M., Gerardo C. (2021)
The aim of this study was to evaluate by simulation the accuracy of the prediction of the breeding value according to the heritability of the trait and the number of progenies. Populations were simulated with six progenies for males (n = 15, 30, 50, 75, 100 and 150) and three for females (n = 1, 2 and 3) and characteristics with three heritability (h2 = 0.098, 0.22 and 0.56). The prediction of the breeding values was calculated by the method of the best unbiased linear predictor and the accuracy was calculated from the diagonal of the matrix of the mixed model equation. It was found that the higher heritability the accuracy was also higher in all scenarios. Regarding the number of progenies per male, accuracy values above 0.9 were obtained when the progeny was greater than 30. In the case of females, the highest accuracies were 0.56 for heritability with values of 0.71, 0.74 and 0.76 for 1, 2 and 3 offspring, respectively. The accuracy of the prediction of the breeding value in traits with heritability similar to those of importance in alpacas was greater when the number of progenies per male increased and when the heritability of the trait was greater.